Nursing of a patient with subcutaneous hematoma after peripherally inserted central catheter placement treated with Sanhuang ointment external application (三黄膏外敷治疗经外周静脉置入中心静脉导管穿刺后血肿1例的护理体会) - ZHOU Zhijuan (周志娟); CHEN Chang (陈嫦); HUANG Jinlan (黄金兰) (Association of Integrative Nursing, 2023)
This paper summarized the nursing of a patient with subcutaneous hematoma after peripherally inserted central catheter (PICC) placement treated with Sanhuang ointment external application. Based on the Traditional Chines Medicine syndrome differentiation, external application of Sanhuang ointment in combination with routine nursing was applied to relive the discomfort, improve hematoma resolution and ensure the smooth progress of chemotherapy. (本文总结1例三黄膏外敷治疗经外周静脉置入中心静脉导管(PICC)穿刺后血肿的护理经验。基于中医辨证分型, 采用三黄膏中药封包外敷中医适宜技术干预, 同时配合常规护理, 可减轻肿瘤患者皮下血肿的不适感, 加速血肿消退, 保障后续化疗的稳定进行。)